Mental health indices may fully mediate the relationship between morningness–eveningness and disease control among adult asthma patients. (3rd October 2022) - Mokros, Łukasz; Witusik, Andrzej; Szydłowska, Dorota; Jankowski, Konrad S.; Kuna, Piotr; Pietras, Tadeusz
Abstract: Objective: The aim of this study was to assess the association between morningness–eveningness and disease control with consideration of mental state as a mediator and the control of confounding factors among adult asthma patients. Methods: This is a cross-sectional study, which included a nonrandom sample of N = 66 patients from an outpatient unit with a confirmed asthma diagnosis, who gave an informed consent and completed a set of questionnaires: a survey comprising questions about sociodemographic and clinical characteristics, the Asthma Control Test (ACT), the Composite Scale of Morningness (CSM), and the General Health Questionnaire (GHQ-28). Mediation models were created separately for each GHQ-28 dimension (somatic symptoms, anxiety/insomnia, social dysfunction and depressive symptoms), for a total score and for four GHQ-28 dimensions together, considered as mediators. Results: Low morning affect was related to poor disease symptom control among patients with asthma. The effect was fully mediated by non-psychotic mental health indices. Evening-time preference was associated with a rise in asthma control, and mediated by somatic symptoms and anxiety/insomnia, when controlled for morning affect. Conclusions: The current study underlines the significance of assessment of both individual morningness–eveningness preference and mental health in the management of asthma symptoms.